Characteristics of flow behavior and heat transfer in the grooved channel for pulsatile flow with a reverse flow. (February 2020) - Pan, Junxiu; Bian, Yongning; Liu, Yang; Zhang, Fengge; Yang, Yunjie; Arima, Hirofumi
Highlight: The flow characteristics in the grooved channel for pulsatile flow with a reverse flow havebeen captured. The flow is less stable in the deceleration phase for the forward flow ( t = 0.375–0.627) and thetransition phase between forward flow and reverse flow (around t = 0.627 and t = 0.873). There is a phase lag between the instantaneous volume flow rate and the overall pressure drop for pulsatile flow. Abstract: The present study investigates the flow behavior and heat transfer in the grooved channel for pulsatile flow with a reverse flow by experimental and numerical approaches at different Strouhal numbers (from 0 to 0.125) and different oscillatory fractions (from 0.6 to 1.4). The pulsatile flow patterns are visualized by the aluminum dust method, and the numerical model is validated by experimental results. It is observed that the flow is less stable in the reverse acceleration phase. At the same time, streamlines, temperature and vorticity in the upper and lower grooves are asymmetrical. Besides, this instability leads to a remarkable mix between the groove and the main flow and contributes to the enhancement of heat transfer. In addition, the onset of the unstable state gradually delays and the duration of the unstable state reduces with the increase of Strouhal number during the test range when the net Reynolds number is 375 and the oscillatory fraction is 1.4. Also, it demonstrates that the time-averaged Nusselt number increases with oscillatory fraction which suggests that the imposed reverse flow is capable of improving the heat transfer. It is further revealed that the maximum heat transfer enhancement factor is 2.74 when the oscillatory fraction is 1.4.